The level of people perception towards the financial performance of Islamic Unit Trust / Nurul Huda Zainal Arifin - Zainal Arifin, Nurul Huda (2010)
The research studies on the relationship of people perception level towards the Islamic unit trust financial performance. The scope of study focuses on the differences and characteristics, factors and people perception towards the Islamic unit trust performance. The objective of study is to determine the relationship between people perception with the trends movement performance of Islamic unit trust. There are two variables which are chosen in this study, are the dependent variable is the level of people perception and the independent variable is financial performance of Islamic unit trust. The data period cover from 2005 to June 2010 (5 years). The results of the study obtained the relationship with good financial performance will influencing the people perception or decision on Islamic unit trust. The final findings indicated that people perception is a huge influence factors towards the Islamic unit trust trends performance.